Characterization of Tn6238 with a New Allele of aac(6′)-Ib-cr - Quiroga, María Paula (2015)
Here, we report that the genetic structure of Tn1331 remained conserved in Argentina from 1989 to 2013 (72 of 73 isolates), with the exception being the plasmid-borne Tn1331-like transposon Tn6238 containing a new aac(6′)-Ib-cr allele recovered from a colistin-resistant Klebsiella pneumoniae clinical isolate. A bioinformatic analysis of aac(6′)-Ib-like gene cassettes suggests that this new aac(6′)-Ib-cr allele emerged through mutation or homologous recombination in the Tn1331 genetic platform. Tn6238 is a novel platform for the dissemination of aminoglycoside and fluoroquinolone resistance determinants.